Diverse Epigenetic Regulations of Macrophages in Atherosclerosis - Yang, Hongmei; Sun, Yue; Li, Qingchao; Jin, Fengyan; Dai, Yun (Frontiers in Cardiovascular Medicine, 2022)
Emerging research on epigenetics has resulted in many novel discoveries into atherosclerosis (AS), characterized by chronic inflammation primarily driven by macrophages. The bulk of evidence has demonstrated the central role of epigenetic machinery in macrophage polarization to pro- (M1-like) or anti-inflammatory (M2-like) phenotype. An increasing number of epigenetic alterations and their modifiers involved in reprogramming macrophages by regulating DNA methylation or histone modifications (e.g., methylation, acetylation, and recently lactylation) have been identified. They may act to determine or skew the direction of macrophage polarization in AS lesions, thereby representing a promising target. Here we describe the current understanding of the epigenetic machinery involving macrophage polarization, to shed light on chronic inflammation driving onset and progression of AS, using atherosclerosis as a prototypic example, and discuss the challenge for developing effective therapies targeting the epigenetic modifiers against AS, particularly highlighting a potential strategy based on epigenetically-governed the repolarization from M1-like to M2-like phenotype.